Response of soil organic matter indices and fractions after 37 years of wheat production management practices in semi-arid South Africa. Issue 2 (14th March 2020) - Motema, T; Kotzé, E; Loke, PF; du Preez, CC
Abstract : The current study evaluated the long-term response of soil organic matter (SOM) indices and fractions on wheat production management practices in the semi-arid region of South Africa. The treatments included three tillage methods (no-tillage, stubble mulch and ploughing), two residue disposal methods (no-burning and burning), and two weed control methods (chemical and mechanical). The soil samples were collected at 0–50, 50–100, 100–150, 150–250, 250–350 and 350–450 mm depth intervals to quantify total carbon (C), total nitrogen (N), C:N ratio, fulvic acid (CFA ) humic acid, (CHA ) and CHA :CFA ratio. Tillage methods significantly increased total C, CFA and CHA in the majority of the soil layers as compared to total N and C:N ratio. Residue disposal methods had few significant differences in total C, total N and C:N ratio. Weeding methods and treatment interactions had no significant difference in SOM indices and fractions. The results suggest that SOM of this semi-arid region, could be improved by tillage practices that encourage accumulation of crop residues rather than using mouldboard ploughing. Even though the grain yield was not affected by management practices, if the aim is towards the sustainable use of soil, soil quality should be prioritized more than the grain yield.